Effect of Family Education and Social Environment to Student Characteristic (Dinamika Pendidikan, 2017)
The research aims to know whether or not an influence of family education and social environment on the characteristics of students during the accounting lesson at class XI IPS SMA Negeri I Pati; to know whether or not an influence of social environment on the characteristics of students during the accounting lesson at class XI IPS SMA Negeri I Pati; and to know whether or not an influence between family education and social environment on the characteristics of students during the accounting lesson at class XI IPS SMA Negeri I Pati. The population in this research is 71 students of class XI SMA Negeri I Pati. Method of data analysis in this research consists of percentage descriptive analysis, descriptive statistic, prerequisite test covering normality test and linearity test, multiple linear regression analysis, classical assumption test covering multicollinearity test and heteroscedasticity test, hypothesis test covering simultaneous test (F), coefficient of simultaneous determination (R2), partial test (t), and partial determinant coefficient (r2). Results shows that family education and social environment both simultaneously and individually have positive impacts on the student characteristics.